GENETIC PREDISPOSITION TO PERI-IMPLANTITIS AND THROMBOSIS IN DENTAL IMPLANTS - Adubetska, A.Y.; Dienha, O.V.; Dienga, A.E.; Verbytska, T.H.; Shnaider, S.A.; Pyndus, T.O.; Pyndus, V.B. (World of Medicine and Biology, 2023)
The study was dedicated to determining the association of interleukin-1 (IL1B C3953T), tumor necrosis factor (TNF G-308A) and platelet fibrinogen receptor (ITGB3 T1565C) polymorphisms with early complications in dental implantation. The study group consisted of 22 patients aged 25–55 years with dental implant complications and loss. The control group consisted of 14 patients with long-term dental implants and no implant complications. The distribution of alleles and genotypes of the single nucleotide polymorphism T1565C of the ITGB3 rs5918 gene was different between the study groups. The minor C allele of the T1565C polymorphism of the ITGB3 rs5918t gene increased the risk of thrombosis in the TC allele model. The heterozygous TC genotype was also associated with an increased risk of thrombosis, which is consistent with the dominant inheritance model of CT+CCTT.